Методы повышения надежности системы управления интеллектуальным городом - Гладий, Л. В.; Фауаз, Саид Халава (ХНУРЭ, 2011)
The concept an intelligent city is a new stage for development of an infrastructure of a city with considerable improvement of living conditions of its inhabitants. Service-oriented architecture- is one of the most perspective technologies of construction of the distributed global network. Its basic advantages are loosely coupled of applications, independence of the programming language and platform that is especially important for a heterogeneous network of a city. Reliability and ensuring availability of services is one of the most important characteristics of such network. In working it is offered to use a method dynamic replication for ensuring availability of services.
Keywords: проект «интеллектуальный город»; управление городом